Pengabdian Masyarakat Melalui Pendataan Kemiskinan Dengan Aplikasi BANGKIT - Dewi, Niluh Okta Prema; Arza, Rhaka A.; Setiawan, Irfan; Hutasuhut, Zaki Fauza (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
Accurate poor population data is the basis needed by the government to carry out poverty alleviation efforts. The BANGKIT application is a forum for the government to classify the level of poverty of the population starting from the level of very poor, poor, vulnerable to poor, and not poor. The purpose of this community service activity is to analyze how the use of the BANGKIT application affects the accuracy of the poverty administration system in Garawastu Village. The activity method is carried out through three stages, namely preparation, implementation and evaluation. Population data collection using the BANGKIT application for 129 families registered as poor is carried out directly by filling in poor population data into the digital form available in the BANGKIT application. Based on community service in Garawastu village, it was found that there were still many poor population data that were not on target, where there were still many residents with low economic levels who were not included in the list of poor people. The results of poverty data collection carried out by the community service team through the BANGKIT application for poor people in Garawastu Village showed that of the 129 families registered as poor in the BANGKIT application, only 123 families were verified and validated because 6 families died and moved. Other results found that there are still many data on poor people that are not on target, where there are still many people with low economic levels who are not included in the list of poor people.